High sensitivity absorption spectroscopy of acetylene near 770 nm. (January 2023) - Lyulin, O.M.; Vasilchenko, S.S.; Perevalov, V.I.
Highlights: CRDS spectrum of acetylene in the 770 nm region. First publication of the acetylene line intensities in the 770 nm region. Spectroscopic constants for seven bands. Vibrational transition moments squared and Herman-Wallis parameters for seven bands. Recommended line list of acetylene for the 12887–13084 cm −1 region. Abstract: The Cavity Ring-Down Spectra (CRDS) of acetylene were recorded in the 12933–13087 cm −1 region with sensitivity of 2 × 10 −11 cm −1 . Six bands of 12 C2 H2 and one band of 12 C 13 CH2 were assigned in these spectra. The 3ν1 +ν3 band is the strongest one lying in this region. The line positions and intensities were recovered from the recorded spectra. The line intensities in this region are reported for the first time. The line positions were modeled using the traditional power series expression in terms of the angular momentum quantum number for an isolated band. The line intensities were modeled using the vibrational transition dipole moment squared and the Herman-Wallis parameters. The recommended line list of acetylene was prepared for the 12887–13084 cm −1 region. It is based on the calculated line parameters. But in the case of the perturbations, the calculated line parameters are substituted by the observed ones. The harmonic basis state compositions of the upper states of the two bands at 12991.08 and 12988.75 cm −1 were considered in detail.